Diseases Problems in Vegetable Production - Gupta ,S.k; Thind, T.S (Jodhpur Scientific publishers, 2006)
important diseases of vegetables
symptoms pathogen epidemiology losses
Keywords: symptoms pathogen epidemiology losses